2008
DOI: 10.3748/wjg.14.607
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SOCS-1 in the liver tissues of chronic hepatitis B and its clinical significance

Abstract: AIM:To study the expression of suppressor of cytokine signaling-1 (SOCS-1) in the liver tissues of chronic hepatitis B (CHB) and the clinical significance of this expression. M E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
(36 reference statements)
2
11
0
Order By: Relevance
“…Zhao et al studied the clinical significance of SOCS1 gene expression in liver tissues of HBV infected patients and confirmed the correlation between SOCS‐1 expression and fibrosis stage as well as expression of SOCS‐1 and the inflammatory grade. In contrast to our observation, this study observed no correlation between SOCS1 expression and LFTs . Likewise, in case of biliary drainage (BD) associated with acute obstructive cholangitis, downregulated expression of SOC1 has also been reported to increase regenerative response coupled with upregulation of hepatocyte growth factor (HGF) signaling.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Zhao et al studied the clinical significance of SOCS1 gene expression in liver tissues of HBV infected patients and confirmed the correlation between SOCS‐1 expression and fibrosis stage as well as expression of SOCS‐1 and the inflammatory grade. In contrast to our observation, this study observed no correlation between SOCS1 expression and LFTs . Likewise, in case of biliary drainage (BD) associated with acute obstructive cholangitis, downregulated expression of SOC1 has also been reported to increase regenerative response coupled with upregulation of hepatocyte growth factor (HGF) signaling.…”
Section: Discussionsupporting
confidence: 58%
“…Zhao et al studied the clinical significance of SOCS1 gene expression in liver tissues of HBV infected patients and confirmed the correlation between SOCS‐1 expression and fibrosis stage as well as expression of SOCS‐1 and the inflammatory grade. In contrast to our observation, this study observed no correlation between SOCS1 expression and LFTs .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…39 The regulatory role of SOCS1 in oxidative stressinduced apoptosis has also been investigated to determine the role of SOCS1 in inhibition of cellular apoptosis. 40 Our study investigated expression of SOCS1 before and after glucocorticoid treatment and found that increased transcription levels of SOCS1 were positively associated with the MELD score preand post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Complications may occur following corticosteroid treatment, such as bleeding, infections or even enhancement of HBV replication. 6,39 Although still controversial, many research studies suggest that inhibition of the inflammatory response is an important advantage of corticosteroids. Insufficient blood samples prevented us from analyzing a larger selection of genes for detection.…”
Section: Discussionmentioning
confidence: 99%